2000
DOI: 10.1023/a:1006486319848
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of mammographic densities in Hawaii

Abstract: Epidemiologic evidence suggests that mammographic densities are markers of breast cancer risk. This project investigated the relation between breast cancer and densities in women of Chinese, Japanese, Filipino, Native Hawaiian, and Caucasian ancestry. Mammograms from breast cancer cases and from healthy controls were compared using a computer-assisted method of mammographic density assessment. From 1991 to 1997, 935 cases of breast cancer were diagnosed at Kaiser Permanente in Hawaii; for 647 (69%) subjects, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 14 publications
2
50
0
Order By: Relevance
“…The value was similar to those reported in other studies (Boyd et al, 1982;Brisson et al, 1984;Van Gills et al, 1999). Maskarinec and Meng (2000) reported associations of percent density with breast cancer risk in ethnic groups in Hawaii. A relatively low OR ( ¼ 1.4 for X50% vs o10%) was observed for Asian women including Chinese, Filipinos, and Japanese, but a similarly low OR ( ¼ 1.8) was also noted for Caucasian women in their study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The value was similar to those reported in other studies (Boyd et al, 1982;Brisson et al, 1984;Van Gills et al, 1999). Maskarinec and Meng (2000) reported associations of percent density with breast cancer risk in ethnic groups in Hawaii. A relatively low OR ( ¼ 1.4 for X50% vs o10%) was observed for Asian women including Chinese, Filipinos, and Japanese, but a similarly low OR ( ¼ 1.8) was also noted for Caucasian women in their study.…”
Section: Discussionsupporting
confidence: 91%
“…These methods have included the estimation of the percentage of mammographically detected fibro-glandular breast tissue with epithelial and connective tissue elements (as mammographic density). Harvey and Bovbjerg (2003) reviewed 12 studies reporting the association of mammographic density measured with quantitative methods to breast cancer risk (Boyd et al, 1982(Boyd et al, , 1995Brisson et al, 1982Brisson et al, , 1984Brisson et al, , 1989Wolfe et al, 1987;Saftlas et al 1991;Byrne et al, 1995;Kato et al, 1995;Van Gills et al, 1999;Lam et al, 2000;Maskarinec and Meng, 2000). All of these studies have shown moderate to strong associations of increased breast cancer risk with increased levels of mammographic density.…”
mentioning
confidence: 99%
“…Fifteen independent studies (ten case-control studies and five cohort or case-control studies nested in cohorts) with a total of 6274 cases of breast cancer and 11 638 controls have used quantitative approaches (Boyd et al 1982, Brisson et al 1982, 1984, 1989, Wolfe et al 1987, Saftlas et al 1991, Byrne et al 1995, Kato et al 1995, van Gils et al 1998, Maskarinec & Meng 2000, Thomas et al 2002, Ursin et al 2003, Torres-Mijia et al 2005; Table 1). All of them found an increased risk of breast cancer associated with more extensive density.…”
Section: Review Of Methodologymentioning
confidence: 99%
“…It is strongly associated with breast cancer risk [9,10], is modifiable [11][12][13], and changes in this factor have recently been associated with changes in risk [14]. Although individual dietary components have been exam ined with breast density, only one study has examined the association of dietary patterns with breast density [15].…”
Section: Introductionmentioning
confidence: 99%